PEMANFAATAN MEDIA SCRATCH UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIS SISWA SD (JS (JURNAL SEKOLAH), 2024)
Abstract: Mathematics is one of the important subjects in elementary school (SD). However, many students find it difficult and unmotivated to learn mathematics. This can cause low mathematics learning outcomes. One effort to increase motivation to learn mathematics is to use interesting and interactive learning media. One of the media that can be used is Scratch. Scratch is a visual programming language that is easy to use and can be used to create various kinds of projects, including mathematics learning projects. This research aims to explore the use of Scratch media in increasing elementary school students' mathematical learning motivation. This research uses the Systematic Literature Review (SLR) method to analyze relevant literature. The research results show that Scratch media can increase elementary school students' mathematical learning motivation. This is proven by several indicators, such as increased interest in learning, active participation in learning, and better learning outcomes. The research results show that the use of Scratch media significantly increases students' interest in learning and triggers higher motivation in understanding mathematical concepts, providing important support for innovative and technology-oriented learning approaches in improving the quality of education at the elementary level. Based on the results of this research, it is concluded that Scratch media can be an effective alternative for increasing elementary school students' mathematical learning motivation. The use of Scratch media in mathematics learning needs to continue to be developed and implemented widely in schools. Keyword: Scratch Media, Learning Motivation, Mathematics, Elementary School Students Abstrak: Matematika merupakan salah satu mata pelajaran penting di sekolah dasar (SD). Namun, banyak siswa yang merasa kesulitan dan tidak termotivasi untuk belajar matematika. Hal ini dapat menyebabkan rendahnya hasil belajar matematika. Salah satu upaya untuk meningkatkan motivasi belajar matematika adalah dengan menggunakan media pembelajaran yang menarik dan interaktif. Salah satu media yang dapat digunakan adalah Scratch. Scratch adalah bahasa pemrograman visual yang mudah digunakan dan dapat digunakan untuk membuat berbagai macam projek, termasuk projek pembelajaran matematika. Penelitian ini bertujuan untuk mengeksplorasi pemanfaatan media Scratch dalam meningkatkan motivasi belajar matematis siswa SD. Penelitian ini menggunakan metode Systematic Literature Review (SLR) untuk menganalisis literatur yang relevan. Hasil penelitian menunjukkan bahwa media Scratch dapat meningkatkan motivasi belajar matematis siswa SD. Hal ini dibuktikan dengan beberapa indikator, seperti peningkatan minat belajar, partisipasi aktif dalam pembelajaran, dan hasil belajar yang lebih baik. Hasil penelitian menunjukkan bahwa pemanfaatan media Scratch secara signifikan meningkatkan minat belajar siswa serta memicu motivasi yang lebih tinggi dalam memahami konsep-konsep matematika, memberikan dukungan penting bagi pendekatan pembelajaran yang inovatif dan berorientasi pada teknologi dalam meningkatkan kualitas pendidikan di tingkat dasar. Berdasarkan hasil penelitian ini, disimpulkan bahwa media Scratch dapat menjadi alternatif yang efektif untuk meningkatkan motivasi belajar matematis siswa SD. Penggunaan media Scratch dalam pembelajaran matematika perlu terus dikembangkan dan diimplementasikan secara luas di sekolah-sekolah.Kata Kunci: Media Scratch, Motivasi Belajar, Matematika, Siswa SD